2009
DOI: 10.1073/pnas.0810932106
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the ethylmalonyl-CoA pathway by using 13 C metabolomics

Abstract: The assimilation of one-carbon (C1) compounds, such as methanol, by serine cycle methylotrophs requires the continuous regeneration of glyoxylate. Instead of the glyoxylate cycle, this process is achieved by a not yet established pathway where CoA thioesters are known to play a key role. We applied state-of-the-art metabolomics and 13 C metabolomics strategies to demonstrate how glyoxylate is generated during methylotrophic growth in the isocitrate lyase-negative methylotroph Methylobacterium extorquens AM1. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
243
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(254 citation statements)
references
References 31 publications
9
243
0
2
Order By: Relevance
“…1) (30)(31)(32)(33)40), and mutants in these genes also show defects in growth on both C 1 and C 2 compounds that are rescued by the addition of glyoxylate or glycolate (7,11,30). Of these genes, only those involved in generating active methylmalonyl-CoA mutase showed higher expression in cells grown on ethylamine than succinate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) (30)(31)(32)(33)40), and mutants in these genes also show defects in growth on both C 1 and C 2 compounds that are rescued by the addition of glyoxylate or glycolate (7,11,30). Of these genes, only those involved in generating active methylmalonyl-CoA mutase showed higher expression in cells grown on ethylamine than succinate.…”
Section: Discussionmentioning
confidence: 99%
“…This metabolism requires the conversion of acetyl-coenzyme A (CoA) to glyoxylate, which occurs via a novel pathway in which acetyl-CoA is converted to methylsuccinyl-CoA via acetoacetyl-CoA, ß-hydroxybutyryl-CoA, and ethylmalonyl-CoA (30)(31)(32)(33). Recently, the steps involved in the conversion of methylsuccinyl-CoA to glyoxylate have been elucidated, and the pathway has been termed the ethylmalonyl-CoA (EMC) pathway (1,19,20,40). Careful labeling measurements coupled to measurements of intermediates has confirmed that, during the growth of M. extorquens AM1 on methanol, methylsuccinyl-CoA is converted to glyoxylate and propionyl-CoA via mesaconyl-CoA and ß-methylmalyl-CoA (40).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the ethylmalonyl-CoA pathway, which operates in ecologically relevant species, such as many alphaproteobacteria (Methylobacterium, Rhodobacter) and actinomycetes (Streptomyces), was discovered (41,44,79,92,110). In this acetylCoA assimilation strategy, two carboxylation reactions occur.…”
Section: Carboxylases In Assimilatory Pathwaysmentioning
confidence: 99%
“…32 It is rational to suggest that accumulation of acetyl-CoA molecules, acetyl-CoA being one of the final products of every β-oxidation cycle, leads to coupling of acetyl-CoA with propionyl-CoA provided by the ethylmalonylCoA pathway. The fact that 7-octenoic acid yields more acetyl-CoA than 5-hexenoic acid explains why 3HV was more abundant when the longer co-substrate was fed.…”
Section: Question: Does Methylobacterium Extorquens Possess a Eukaryomentioning
confidence: 99%